Bid from the Association for the Advancement of Wound Care. (1st March 2022) - Bryant, Ruth; Milne, Catherine; Bohn, Gregory; Couch, Kara; Waters, Nicola; Bates-Jensen, Barbara
Abstract : The Association for the Advancement of Wound Care sets out its bid for the WUWHS 2026 Congress to be held in Chicago, Illinois, US.